Properties of t‐zirconia prepared by a composite‐assisted nonhydrolytic sol‐gel. Issue 1 (11th July 2018) - Warwar Damouny, Christine; Khoury, Christine; Gazit, Oz M.
Abstract: High surface area and highly crystalline tetragonal Ni‐Si‐doped ZrO2 samples were prepared using a nonhydrolytic sol‐gel method. The synthesis involved the condensation of zirconium chloride and isopropyl ether in the presence of a chitosan‐based composites containing Ni and Si (Ni@Si‐CS), followed by calcination to remove the CS. The interactions between the zirconium precursor and the Ni@Si‐CS composites were studied and correlated with the effect on morphologies, crystalline structure, phase compositions, and surface area. These parameters were evaluated for different Ni@Si‐CS to ZrO2 mass ratios. It was found that increasing the concentration of Ni@Si‐CS composite led to smaller grains of ZrO2 nanocrystals and an overall material with a higher surface area. The stability of the tetragonal/cubic phases following calcination at 800°C was correlated with the presence of low amounts of Ni 2+ in the sublattice of ZrO2 and the presence of the Si‐chitosan, which acted as steric stabilizer.